The Academic Problems of Family Counseling Diploma Students At Saudi Universities based on some Variables (Journal Of Educational and Psychological Researches, 2022)
The research aims to identify the academic problems of family counseling diploma students at Saudi Universities. In addition, to identify the differences in these problems according to gender, marital status, place of study, academic specialization, and GPA. The sample consisted of (491) students. The researcher has used one questionnaire for academic problems prepared by the researcher.  The research revealed the following results: There were academic problems among family counseling diploma students at Saudi Universities, the most problems were related to the systems and administrations of the university, then the field training, the buildings, classrooms and campus facilities, then the academic courses, after that the exams, then the vocational knowledge, then the academic schedules, then university professor, and finally the vocational skills. Also, there were no statistically significant differences in all dimensions of academic problems and the whole score according to gender except the exams the differences were in favor of male students. There were statistically significant differences at (0.05) in vocational skills according to marital status the differences were in favor of unmarried students, and there were statistically significant differences at (0.05) in the academic schedules, the field training, and the buildings, classrooms, and campus facilities and the whole score of academic problems according to marital status the differences were in favor of married students,. There were statistically significant differences at (0.05) in all dimensions of academic problems and the whole score except the buildings, classrooms and campus facilities according to the place of study the differences in favor of students at King Faisal University and the University of Tabuk. There were statistically significant differences at (0. 05) in the academic courses, academic schedules, and exams according to academic specialization the difference was in favor of students of arts and education specialization, and there were statistically significant differences at (0. 05) in the field training and buildings, classrooms, and campus facilities in favor of students of sciences and education specialization. There were no statistically significant differences in all dimensions of academic problems and the whole score according to GPA.